Estimation Of Productivity Level Of Sampolawa Bay, South Buton District, South East Sulawesi - Cahyani, Waode Sitti; Bugis, Nila Nikmatia; Hasanah, Nur; Purnamasari, Wa Ode Dian (AgriSains, 2020)
The coastal area is an area that is vulnerable to excessive nutrient input. Excessive intake of nutrients can disrupt the balance of the ecosystem in Sampolawa Bay because it is suspected to be the cause of eutrophication in the water column. This study aims to estimation of productivity level in Sampolawa Bay. The study was conducted in July 2020. Determining the productivity level of the waters using the TRIX method by collecting data on phosphate, nitrogen, dissolved oxygen and chlorophyll-a. The results showed the productivity level in Sampolawa Bay ranged from 0.5271 to 0.8735 in the category of oligotrophic or no eutrophication.